Engagement with Kenya Dairy Board on ex-ante impact assessment of proposed new regulations governing the national dairy sector - CGIAR Research Program on Livestock (2020)
The ILRI contribution used a methodology adjusted from Kaitibie et al (2010). The report on data collected from milk traders will be finalized in 2021 (delayed due to COVID-19).